2014
DOI: 10.31931/fmbc.v17i2.2014.60-67
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Dna Variation in the Eastern Pondmussel, Ligumia nasuta (Bivalvia: Unionoida), in the Great Lakes Region

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 20 publications
2
10
1
Order By: Relevance
“…In the western basin of Lake Erie, S. nasutus was consistently found to be the second or third most common unionid species in historical surveys (Nalepa, Manny, Roth, Mozley, & Schloesser, ). Currently, only remnant populations are present across its previous range in the Great Lakes (COSEWIC, ; Michigan Natural Features Inventory, ; Scott, Begley, Krebs, & Zanatta, ; Zanatta et al, ). Despite the large number of historical populations and apparent ease of dispersal into new habitats, the decline and loss of S. nasutus populations is cause for conservation concern.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In the western basin of Lake Erie, S. nasutus was consistently found to be the second or third most common unionid species in historical surveys (Nalepa, Manny, Roth, Mozley, & Schloesser, ). Currently, only remnant populations are present across its previous range in the Great Lakes (COSEWIC, ; Michigan Natural Features Inventory, ; Scott, Begley, Krebs, & Zanatta, ; Zanatta et al, ). Despite the large number of historical populations and apparent ease of dispersal into new habitats, the decline and loss of S. nasutus populations is cause for conservation concern.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study on the phylogeography of S. nasutus using mitochondrial DNA sequences found limited genetic variation within the Great Lakes region. Scott et al () compared the within‐species genetic diversity of two maternally inherited mitochondrial DNA gene regions, finding low genetic diversity within the Great Lakes region. This result suggested that the source population was a single, small founder group or a larger group with low genetic variation (Scott et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations